Getting Hired: The Civil Service Act of 1857 - Piva, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1992)
AbstractIn 1857 the Province of Canada passed the Civil Service Act which made a first attempt to define uniform personnel policies for the emerging bureaucracy. Analysis of applications, examination results and appointments to the inside service between September 1857, when applicants first sat for examination, and the end of 1861, when the government undertook an internal survey of public employees, demonstrates that the reform potential of the Act was only partially realized. The introduction of the examination system strongly favoured applicants who resided in the provincial capital. Applicants were most frequently urban middle-class men born either in the United Kingdom or in Canada East. Many were young, although a significant number were over 30 years of age and had extensive labour market experience. Analysis of the employment histories of applicants shows that middle-class careers commonly involved frequent job changes in which workers moved from one employer to another and often back and forth between salaried employment and independence. The Civil Service examination proved elementary, yet it tested basic skills appropriate for the work of most public employees. Although examination results were sufficiently discrete to be used as a competitive examination, decision-makers treated the exercise as a qualifying examination and paid little attention to examination results. Very few successful candidates found employment in the Civil Service; those few were employed at all ranks within the service. Analysis of public employees in 1861 also demonstrates that, although experience was an important factor, seniority did not govern hiring, promotion or salary decisions. The evidence also suggests that patronage played at best a limited role in hiring decisions within the inside service while nepotism continued to exist. In the end The Civil Service Act proved a modest attempt to reform the bureaucracy by creating uniformity in ranks, procedures for appointment and promotion, and, most importantly, salary structures. Its successes proved even more modest.